Thomas Tien Keng-hsin, SVD: The historical greatness of the first Cardinal of China and the Far East Part one - Miotk, Andrzej (Annales Missiologici Posnanienses, 2019)
That fact that Thomas Tien became the first cardinal of China and the Far East surpassed thewildest dreams of Fr. Arnold Janssen, the founder of the Society of the Divine Word (SVD),who had sent the first two missionaries to China in 1879. He was one fruit of Janssen’sdecision and subsequent concentrated involvement of the Society in evangelizing China. Thisstudy gives an insight into historical greatness of Thomas Cardinal Tien Keng-hsin for theUniversal Church, the Society of the Divine Word and local Church in China. He emergesmainly as an iconic figure reflecting the developments in the Chinese Church and played asymbolical role for the universal Church as an important link in the process ofinternationalization of the Church and her subsequent self-actualization as a World Church atVatican II. The study aims at making us aware that Tien’s figure should have an integral placein the systematic and comprehensive research on the as yet little explored mission of theSociety of the Divine Word in China.